Antimicrobial and enzyme activity of mangrove endophytic fungi of southwest coast of India - Maria, G.L.; Sridhar, K.R.; Raviraja, N.S. (International Journal of Agricultural Technology, 2005)
The antimicrobial potential of 14 endophytic fungi isolated from Acanthus ilicifolius and Acrostichum aureum towards selected bacteria (Bacillus subtilis, Enterococcus sp., Klebsiella pneumoniae, Pseudomonas aerugionsa, Salmonella typhi and Staphylococcus aureus) and fungi (Candida albicans and Trichophyton metagrophytes) was tested using ethyl acetateextract of fungi cultivated under solid-state fermentation (SSF). Aspergillus spp. showed promising antagonistic features. All test bacteria were inhibited by sterile isolate MSI 1. Cumulospora marina and Pestalotiopsis sp. showed considerable inhibition on Gram-positive and Gram-negative bacteria. Crude ethyl extracts derived from submerged fermentation (SmF) of four endophytes showing positive results were further evaluated. Aspergillus sp. 3 and Pestalotiopsis sp. inhibited many bacteria and Candida albicans, while inhibition by Aspergillus sp. 2 and MSI 1 was confined to bacteria. Crude ethyl acetate extracts purified by TLC of four endophytes grown under SmF showed many fluorescent fractions. Two fractions of Aspergillus sp. 3 showed high antimicrobial activity. One of the fractions of Pestalotiopsis sp. showed considerable inhibition of Bacillus subtilis, Staphylococcus aureus and Candida albicans. Seven endophytic fungi were assessed for the production of extracellular enzymes (amylase, cellulase, chitinase, laccase, lipase, protease and tyrosinase) by culture plate method. Cellulase and lipase activity was present in all fungi, while amylase and protease in a few. No fungi exhibited chitinase, laccase and tyrosinase activity. Enzyme production of Pestalotiopsis sp. (cellulase by SmF; xylanase, pectinase and protease by SSF) at pH 7 and pH 9 during 3-15 days of fermentation was assessed. The Cellulase activity was highest at pH 7 on 6th day, while xylanase activity was highest on 9th day at pH 9. Highest activity of pectinase was seen on 6th (pH 7) and 9th days (pH 9). Protease activity was highest on 6th day at pH 7 and 9.